Komparasi Kebijakan Pengembangan Bahan Bakar Nabati di Indonesia dan Kolombia: Dilema Antara Pasar, Kapasitas Produksi dan Daya Serap - Ari Paminto; Raldi Koestoer; Mahawan Karuniasa; Evi Frimawaty (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2022)
In recent years the world has experienced ups and downs in biofuel production, from an annual figure of 9.2 million tonnes in 2000 to 95.4 million tonnes in 2018.National policies are not made to stabilize the sugar and palm oil sectors, but to develop the industry. National BBN (Biofuel). The aim of this paper is to analyze biofuel development policies between Colombia and Indonesia in relation to the sugar and palm oil sectors. The method used is descriptive analysis by means of literature studies, data collection, and analysis of biofuel development policies in Indonesia and Colombia. The Colombian government provides incentive mechanisms to promote biofuel fuels, including a mandate for biofuel blending. The pricing policy is set by considering the opportunity cost of using alternative raw materials. Meanwhile in Indonesia, the mandatory biofuel policy is in order to reduce dependence on imported diesel oil in order to save the country’s foreign exchange. In Colombia, the adoption of a biofuel policy has allowed the creation of a market for ethanol and biodiesel which comes partly from the substitution of sugar production with ethanol production, and the dynamic interaction between palm oil and biodiesel production. In Indonesia, biodiesel production has not been optimal compared to its installed capacity due to political economy and price factors. The low absorption of biodiesel is an indirect obstacle to the sustainability of the national bioenergy program.